What about the mothers? An analysis of maternal mortality and morbidity in perinatal health surveillance systems in Europe - Bouvier-Colle, M-H (Blackwell Publishing Ltd, 2012)
OBJECTIVE: To assess capacity to develop routine monitoring of maternal health in the European Union using indicators of maternal mortality and severe morbidity. DESIGN: Analysis of aggregate data from routine statistical systems compiled by the EURO-PERISTAT project and comparison with data from national enquiries. SETTING: Twenty-five countries in the European Union and Norway. POPULATION: Women giving birth in participating countries in 2003 and 2004. METHODS: Application of a common collection of data by selecting specific International Classification of Disease codes from the ‘Pregnancy, childbirth and the puerperium’ chapter. External validity was assessed by reviewing the results of national confidential enquiries and linkage studies. MAIN OUTCOME MEASURES: Maternal mortality ratio, with distribution of specific obstetric causes, and severe acute maternal morbidity, which included: eclampsia, surgery and blood transfusion for obstetric haemorrhage, and intensive-care unit admission. RESULTS: In 22 countries that provided data, the maternal mortality ratio was 6.3 per 100 000 live births overall and ranged from 0 to 29.6. Under-ascertainment was evident from comparisons with studies that use enhanced identification of deaths. Furthermore, routine cause of death registration systems in countries with specific systems for audit reported higher maternal mortality ratio than those in countries without audits. For severe acute maternal morbidity, 16 countries provided data about at least one category of morbidity, and only three provided data for all categories. Reported values ranged widely (from 0.2 to 1.6 women with eclampsia per 1000 women giving birth and from 0.2 to 1.0 hysterectomies per 1000 women). CONCLUSIONS: Currently available data on maternal mortality and morbidity are insufficient for monitoring trends over time in Europe and for comparison between countries. Confidential enquiries into maternal deaths are recommended.